Simulation and analysis of a novel micro-beam type of MEMS strain sensors - Cuong, Nguyen Chi; Thang, Trinh Xuan; Hoai, Tran Duy; Phuong, Nguyen Thanh; Long, Vu Le Thanh; Ly, Truong Huu; Cuong, Hoang Ba; Thanh, Ngo Vo Ke (Vietnam Journal of Science and Technology, 2019)
A new structure of a micro-strain beam type of Micro-Electro-Mechanical-Systems (MEMS) strain gauge is proposed and simulated. The stress and strain distributions of MEMS strain gauge are evaluated in x and y directions by 2D FEM simulation, respectively. The results showed that the longitudinal stress and strain distributions of strain beam enhance significantly, while the transverse stress and strain distributions are almost unchanged in the whole structure of MEMS strain gauge. High sensitivity of piezoresistive MEMS strain sensors can be designed to detect only one single direction of the stress and strain on the material objects.